Anomalously strong vertical magnetic fields from distant ELF/VLF sources. Issue 7 (29th July 2015) - Silber, Israel; Price, Colin; Galanti, Eli; Shuval, Abraham
Abstract: There are many sources of very low frequency (VLF—3–30 kHz) and extremely low frequency (ELF—3–3000 Hz) radiation in the Earth‐ionosphere waveguide (e.g., lightning and ELF/VLF communication transmitters). At distances of thousands of kilometers from these sources, the vertical component of the ELF/VLF AC magnetic fields is expected to be very weak and several orders of magnitude lower than the horizontal magnetic components. However, measurements in Israel show a relatively strong vertical magnetic component in both the ELF and VLF bands, at the same order of magnitude as the horizontal components. Our measurements suggest that the real Earth‐ionosphere waveguide might often be very different from the theoretical waveguide used in model calculations. In addition, our results imply that using only the horizontal components for direction finding or the absolute magnetic field strength may result in errors, since often a significant fraction of the magnetic field energy hides in the vertical component. Key Points: Strong measured vertical magnetic field component in both the ELF and VLF bands The Earth‐ionosphere waveguide might often be different from that used in models Using only the horizontal magnetic field components may result in errors